Using protein microarray to identify and evaluate autoantibodies to tumor‐associated antigens in ovarian cancer. Issue 2 (3rd December 2020) - Ma, Yan; Wang, Xiao; Qiu, Cuipeng; Qin, Jiejie; Wang, Keyan; Sun, Guiying; Jiang, Di; Li, Jitian; Wang, Lin; Shi, Jianxiang; Wang, Peng; Ye, Hua; et al.
Abstract: The aim of this study was to develop a noninvasive serological diagnostic approach in identifying and evaluating a panel of candidate autoantibodies to tumor‐associated antigens (TAAs) based on protein microarray technology for early detection of ovarian cancer (OC). Protein microarray based on 154 proteins encoded by 138 cancer driver genes was used to screen candidate anti‐TAA autoantibodies in a discovery cohort containing 17 OC and 27 normal controls (NC). Indirect enzyme‐linked immunosorbent assay (ELISA) was used to detect the content of candidate anti‐TAA autoantibodies in sera from 140 subjects in the training cohort. Differential anti‐TAA autoantibodies were further validated in the validation cohort with 328 subjects. Subsequently, 112 sera from the patients with ovarian benign diseases with 104 OC sera and 104 NC sera together were recruited to identify the specificity of representative autoantibodies to OC among ovarian diseases. Five TAAs (GNAS, NPM1, FUBP1, p53, and KRAS) were screened out in the discovery phase, in which four of them presented higher levels in OC than controls ( P  < .05) in the training cohort, which was consistent with the result in the subsequent validation cohort. An optimized panel of three anti‐TAA (GNAS, p53, and NPM1) autoantibodies was identified to have relatively high sensitivity (51.2%), specificity (86.0%), and accuracy (68.6%), respectively. This panel can identify 51% of OC patients with CA125 negative. This study supports our assumption that anti‐TAA autoantibodies can be considered as potential diagnostic biomarkers for detection of OC; especially a panel of three anti‐TAA autoantibodies could be a good tool in immunodiagnosis of OC. Abstract : We developed a noninvasive serological diagnostic approach of ovarian cancer (OC). Autoantibodies can be considered as potential biomarkers for the detection of OC. A panel of three anti‐TAA (GNAS, p53, and NPM1) autoantibodies was identified.